Koreografi Tari Kipas Pada Sanggar Seni Mutiara Minang di Kota Padang Sumatera Barat - Ayuning Dwi Kusrini; Herlinda Mansyur (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to reveal and describe the Fan Dance Choreography at the Minang Pearl Art Studio in Padang City, West Sumatra. This type of research is qualitative research with a descriptive method. The instruments in this study are the researchers themselves and are assisted by supporting instruments such as stationery, cameras and audio recorders. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps of analyzing data are data reduction and data presentation. The results showed that the creation of a dance work is inseparable from the creative process starting from idea discovery, exploration, improvisation, and composition. After finding ideas and ideas from the fan dance, then the dance director contemplated the dance image to be made. Exploration looks for gestures that describe a girl who is strong, firm, but still gentle in behavior as described how gadih minang is. The improvisation stage carried out by dance directors in Fan dance is an experiment with the form of movement obtained from dancers and a variety of movements that are new but developed according to the creativity of dance directors and themes. The improvisation stage is accompanied by an evaluation stage to select and evaluate movements and is adjusted to the theme. In the composition stage, the dance director combines all the various movements obtained from the exploration and improvisation process into a complete dance.